Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1124/jpet.107.133272
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Protection of Phencyclidine-Induced Neurotoxicity in Developing Brain: The Role of Phosphatidylinositol-3 Kinase/Akt and Mitogen-Activated Protein Kinase Kinase/Extracellular Signal-Regulated Kinase Signaling Pathways

Abstract: Phencyclidine (PCP) and other N-methyl-D-aspartate (NMDA) receptor antagonists have been shown to be neurotoxic to developing brains and to result in schizophrenia-like behaviors later in development. Prevention of both effects by antischizophrenic drugs suggests the validity of PCP neurodevelopmental toxicity as a heuristic model of schizophrenia. Lithium is used for the treatment of bipolar and schizoaffective disorders and has recently been shown to have neuroprotective properties. The present study used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
2
22
0
1
Order By: Relevance
“…The antipsychotic, sertindole, and ampakine CX516 (an AMPA receptor modulator) were able to attenuate these deficits in attentional set-shifting (109). Neonatal PCP administration was also associated with apoptosis of GABAergic interneurons in the primary somatosensory, motor, and retrosplenial cortices as well as neurodegeneration in the striatum and hippocampus, an effect that could be attenuated by treatment with lithium (110, 111). …”
Section: Neurodevelopmental Animal Models Of Schizophreniamentioning
confidence: 99%
“…The antipsychotic, sertindole, and ampakine CX516 (an AMPA receptor modulator) were able to attenuate these deficits in attentional set-shifting (109). Neonatal PCP administration was also associated with apoptosis of GABAergic interneurons in the primary somatosensory, motor, and retrosplenial cortices as well as neurodegeneration in the striatum and hippocampus, an effect that could be attenuated by treatment with lithium (110, 111). …”
Section: Neurodevelopmental Animal Models Of Schizophreniamentioning
confidence: 99%
“…These findings imply that transient disruptions in NMDAR-related signals during this critical period can underpin long-term abnormalities. However, although several studies have suggested possible mechanisms, such as NMDAR antagonist-induced apoptotic neurodegeneration Hansen et al 2004 ;Ikonomidou et al 1999 ;Lei et al 2008 ;Lema Tome et al 2006 ;Xia et al 2008), it still requires further investigation.…”
Section: Introductionmentioning
confidence: 97%
“…In support of this, it has been shown that postnatal PCP injections resulted in lower levels of phosphorylated ERK1/2 in the hippocampus of juvenile rats compared to controls 49,50 . Furthermore PCP treatment in organotypic brain slice culture from rats showed decreased phosphorylation levels of MEK1/2 and ERK1/2, both downstream signaling partners of p75 cell survival pathways, suggesting that PCP may induce cell death through the inhibition of the MEK/ERK/1/2 prosurvival pathways 51 ( Figure 2). The expression pattern of p75 and TROY seems to recover over time, normalizing around adolescence as there are no significant differences in either p75 or TROY expression in the 5 week old rats (p>0.05).…”
Section: Alterations Of P75 Troy and Myt1 In A Pcp Induced Neurodevementioning
confidence: 99%